2017
DOI: 10.1159/000480343
|View full text |Cite
|
Sign up to set email alerts
|

Non-Genomic Action of Androgens is Mediated by Rapid Phosphorylation and Regulation of Androgen Receptor Trafficking

Abstract: Background: Testosterone is critical for maintaining spermatogenesis and male fertility. The accomplishment of these processes requires the synergistic actions of the classical and non-classical signaling pathways of androgens. Methods: A murine testicular Sertoli cell line, TM4 cell was used to examine androgen actions in Sertoli cells. Western blot analysis and immunofluorescence assay were employed to study the testosterone-induced Androgen receptor (AR) translocation. Protein phosphorylation antibody array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 34 publications
5
38
0
Order By: Relevance
“…previous report has shown membrane-associated AR mediates rapid AKT activation stimulated by androgen (9,25). Consistent with this study, we found androgen-induced AKT phosphorylation at 30 min was blocked in the presence of the KIF5Btail, but not the KIFC3-tail ( Fig.…”
Section: Ar Membrane Trafficking and Signalingsupporting
confidence: 93%
“…previous report has shown membrane-associated AR mediates rapid AKT activation stimulated by androgen (9,25). Consistent with this study, we found androgen-induced AKT phosphorylation at 30 min was blocked in the presence of the KIF5Btail, but not the KIFC3-tail ( Fig.…”
Section: Ar Membrane Trafficking and Signalingsupporting
confidence: 93%
“…Consistent with the previous studies [6,14,17], Western blot analysis using TM4 cells revealed the rapid increase in the phosphorylation of kinase protein kinase B (Akt) (Ser473), Erk1/2 (Thr202/Tyr204), and mitogen activated protein kinase kinase (MEK1/2) (Ser217/221) within 5 min. Knockdown of CSN6 by shRNA inhibited the increase in the phosphorylation caused by testosterone stimulation (Fig.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 87%
“…As described in a previous study, testosterone induces AR translocation to membrane in primary Sertoli cells, with translocation becoming significantly evident within 5 min [14].…”
Section: Identification Of Candidate Proteins By Ms and Bioinformaticsupporting
confidence: 77%
See 1 more Smart Citation
“…Testosterone is known to mediate its effects by two different pathways of action, classical pathway of cytosolic/nuclear androgen receptors and non-classical pathway of membrane-associated androgen receptors (Deng et al 2017). The classical effects of testosterone occur slowly because of the translation of newly synthesized proteins and the non-classical effects of testosterone occur fast due to the rapid phosphorylation of signal molecules (Deng et al 2017). In Experiment 3 of the present study, we did not find the differences of motor behavior and grooming behavior between the rats receiving Hal treatment and the rats receiving Hal concurrent with TP treatment.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%